Reseña de: Olds, Katrina B., Forging the past. The invented histories in Counter-Reformation Spain - Rodríguez Solís, José Javier (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2019)
Reseña de: Reseña del libro de Olds, Katrina B., Forging the past. The invented histories in Counter-Reformation Spain, Yale, UP, 2015, 314 pp., ISBN: 978-0-300-18522-5